Intermediate Algebra (12th Edition)

Published by Pearson
ISBN 10: 0321969359
ISBN 13: 978-0-32196-935-4

Chapter 4 - Section 4.4 - Multiplying Polynomials - 4.4 Exercises: 35

Answer

$12k^{2}+k-6$

Work Step by Step

We are given the expression $(4k+3)(3k-2)$. We can find the product of this expression using the FOIL method. First terms: $4k\times 3k=12k^{2}$ Outer terms: $4k\times-2=-8k$ Inner terms: $3\times 3k=9k$ Last terms: $3\times-2=-6$ Adding together: $12k^{2}+(-8k)+9k+(-6)=12k^{2}-8k+9k-6=12k^{2}+k-6$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.